The Picture Brides: Japanese Issei Women Migration to the United States: A Study on Julie Otsuka’s the Buddha in the Attic - Wulandari, Yeni (Journal of Education for Sustainability and Diversity, 2025)
This study is aimed at exploring the mistreatment, violence and oppressions experienced by the Japanese American Issei women during from the beginning of their migration to the United States and how they adapt to live in the new neighborhood in a new country. This study especially investigates on the first generation of Japanese American women who crossed through the Trans-Atlantic Ocean for marrying the Japanese American men whom they never met before and known from picture sent from the US. Having their status changed as wives once they reached the American land, they have got unjust treatment from not only the men they would married but also from their new environment. In this research, the researcher analyzes the data through collecting from the work by employing the intersectional feminist theory. This study’s goal is to find how they settle their life in the new culture and how the migration influenced their life. This research analyzes the book The Buddha in the Attic by Julie Otsuka. The researcher chose this work because it contained the theme that have the concerns on what happened to the Japanese first women migrants and how they then settle and continue to live there with the identity of the Issei Japanese American women.